Femtosecond Third-Order Non-Linear Optical Properties of Unconstrained Green Fluorescence Protein Chromophores - Ahmed, Md Soif; Biswas, Chinmoy; Banerjee, Dipanjan; Chetti, Prabhakar; Yang, Jye-Shane; Soma, Venugopal Rao; Raavi, Sai Santosh Kumar (Frontiers in Physics, 2022)
We report herein results on the third-order non-linear optical (NLO) properties of four structurally unconstrained green fluorescence protein (GFP) chromophores, namely, 1, 2, 3, and 4. Using experimental techniques and theoretical calculations such as UV–visible spectroscopy, density functional theory (DFT), time-dependent density functional theory (TDDFT), and Z-scan techniques, we have investigated the linear absorption, ultrafast non-resonant third-order optical non-linearities, and the onset of optical-limiting thresholds of these benzylidenedimethylimidazolinone (BDI) dyes. The Z-scan measurements were performed at a wavelength of 800 nm with ∼70 femtosecond (fs) pulses. We have witnessed a strong reverse saturable absorption (fitted to three-photon absorption) for all of the molecules with fs pulse excitation. The valley–peak curves obtained from the closed-aperture Z-scan technique revealed the positive non-linear refractive index (self-focusing) nature of these molecules. We have evaluated the various third-order NLO coefficients (second hyperpolarizability, γ ∼10–33 esu), which were found to be larger than those of similar molecules reported in the recent literature.